ผลของโปรแกรมการบำบัดโดยการเสริมสร้างแรงจูงใจต่อพฤติกรรมการดื่มสุราของผู้ป่วยจิตเภทที่ติดสุรา - มานะศักดิ์ เหลื่อมทองหลาง (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study is a quasi- experimental. The objective were to compare:1) alcohol dependence of schizophrenic patients with alcohol drinking problem who received motivational interviewing dual diagnosis program 2) alcohol dependence of schizophrenic patients with alcohol drinking problem who received motivational interviewing dual diagnosis program measured and those who received regular nursing care. The sample consisted of 40 schizophrenic patients with alcohol drinking problem and then randomly assigned to either experimental or control group, 20 subjects in each groups. Research instruments comprised of 1) Motivational interviewing dual diagnosis program and 2) demograpic questionnaire. All instruments were validated for content validity by 4 professional experts. The reliability of the instruments were reported by Cronbach’s Alpha coefficient of .87 Data were analyzed using descriptive statistics and t-test. The conclusions of this research are as follows: 1. Alcohol dependence of schizophrenic patients with alcohol drinking problem who received the motivational interviewing dual diagnosis program post intervention was significantly lower than that before at p.05 level. 2. Alcohol dependence of schizophrenic patients with alcohol drinking problem who received the motivational interviewing dual diagnosis program post intervention was significantly lower than those who received the regular nursing care, at p.05 level.